PENGARUH MEDIA GAMBAR TERHADAP KEMAMPUAN BAHASA ANAK KELOMPOK B DI RA MARDHATI SKARDA N-III KECAMATAN RAPPOCINI KOTA MAKASSAR - Eka Sumarni; Andi Adam; Sri Sufliati Romba (STKIP Subang, 2023)
The main problem in this research is how to improve children's language skills through picture media in class B at RA Mardhati Skarda N III, Rappocini District, Makassar City. The type of research used is experimental research using a one group pretest design consisting of pretest, treatment and posttest. The subjects of this study were the children of group B, which consisted of 15 children. The results of this study indicate that the average score at the pretest is 6.06% and the average value at the posttest is 19.06%. then this research is also supported by the results of calculations using the Wilcoxon signed rank test in the SPSS 21.0 program (statictical package for Social science) obtained, obtained a significance value of 0.001 here obtained a probability of 0.001 or (P <0.05), which means that H0 is rejected and H1 is accepted.